2021
DOI: 10.3390/w13121681
|View full text |Cite
|
Sign up to set email alerts
|

Graph Convolutional Networks: Application to Database Completion of Wastewater Networks

Abstract: Wastewater networks are mandatory for urbanisation. Their management, including the prediction and planning of repairs and expansion operations, requires precise information on their underground components (manhole covers, equipment, nodes, and pipes). However, due to their years of service and to the increasing number of maintenance operations they may have undergone over time, the attributes and characteristics associated with the various objects constituting a network are not all available at a given time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The calculated AUC values for the training and validation datasets were found to be the same (97.2% and 97.25%, respectively), thus indicating an excellent prediction accuracy (Yesilnacar, 2005). The results show that GCNs significantly improve the performance of the predictions for land susceptibility to wind erosion and support the findings of previous studies, which suggested that GCNs are an efficient graph model for semi-supervised learning (Chen et al, 2018) and constitute a useful tool for completing missing data (Belghaddar et al, 2021). The DL hybrid models (e.g., convolutional neural network-gated recurrent unit (CNN-GRU) and dense layer deep learning-random forest (DLDL-RF)) were also recently shown to be efficient methods for classifying dust sources in the Middle East (Gholami and Mohammadifar, 2022).…”
Section: Assessment Of Gcn Model Performancesupporting
confidence: 82%
“…The calculated AUC values for the training and validation datasets were found to be the same (97.2% and 97.25%, respectively), thus indicating an excellent prediction accuracy (Yesilnacar, 2005). The results show that GCNs significantly improve the performance of the predictions for land susceptibility to wind erosion and support the findings of previous studies, which suggested that GCNs are an efficient graph model for semi-supervised learning (Chen et al, 2018) and constitute a useful tool for completing missing data (Belghaddar et al, 2021). The DL hybrid models (e.g., convolutional neural network-gated recurrent unit (CNN-GRU) and dense layer deep learning-random forest (DLDL-RF)) were also recently shown to be efficient methods for classifying dust sources in the Middle East (Gholami and Mohammadifar, 2022).…”
Section: Assessment Of Gcn Model Performancesupporting
confidence: 82%
“…Using minimal and maximal value bounds chosen by the user, the algorithm allocates the pipe diameters according to Strahler's order [9], thus ensuring the general increase of the diameters from upstream to downstream. When a minimum of 20% of the attributes are available, one may use a semi-supervised learning method to predict the missing values as described in [10].…”
Section: Diameter Estimationmentioning
confidence: 99%
“…Therefore, these applications are not considered as surrogate models. In UDSs, Belghaddar et al (2021) applied GNNs to complete missing values in databases of wastewater networks.…”
Section: Inductive Bias-deep Learningmentioning
confidence: 99%
“…In UDSs, Belghaddar et al. (2021) applied GNNs to complete missing values in databases of wastewater networks. Given its novelty and potential, further research on the GNN architecture is recommended to establish the benefits and limitations of this approach for surrogating UWN models, together with comparisons against already established MLSMs, for example, fully connected neural networks.…”
Section: Research Directionsmentioning
confidence: 99%